Mapping the Discourse: Scientometric Analysis of Affordable Housing Research Trends - Nor Suzylah Sohaimi; Nur Aili Hanim Hanafiah; Azhani Abd Manaf; Tülay Zıvalı (Alanya Üniversitesi, 2024)
Affordable housing is not merely about cost but encompasses quality, safety, and accessibility. The shortage of affordable housing perpetuates cycles of poverty, negatively impacting well-being. Utilizing scientometric techniques —co-authorship analysis, citation network analysis, and keyword co-occurrence analysis— on Scopus data from 1999 to 2024, and employing the VOSviewer tool, the aim of this study is to provide a comprehensive understanding of housing affordability by integrating both monetary and non-monetary factors and identifies 1) the co-authorship, co-occurrence, and countries’ collaboration, and 2) the most cited article in the field. The results reveal key contributors in affordable housing research, highlight influential works, and map publishing trends. The outcomes show that nine different groups exist and actively collaborate worldwide. Waddell’s work, with 873 citations, is the most cited, followed by Monahan with 421 citations. The analysis highlights significant thematic clusters, such as the integration of technological advancements, health considerations, and policy changes in affordable housing research. The study underscores the critical role of social and environmental sciences in addressing housing equity and community well-being. By mapping the current research landscape and forecasting future trajectories, this study provides critical insights for guiding future research, policy development, and societal progress in affordable housing.